2024
DOI: 10.1002/eji.202149641
|View full text |Cite
|
Sign up to set email alerts
|

The “Domino effect” in MASLD: The inflammatory cascade of steatohepatitis

Karlo Mladenić,
Maja Lenartić,
Sonja Marinović
et al.

Abstract: Metabolic dysfunction‐associated steatotic liver disease (MASLD) is an increasingly common complication of obesity, affecting over a quarter of the global adult population. A key event in the pathophysiology of MASLD is the development of metabolic‐associated steatohepatitis (MASH), which greatly increases the chances of developing cirrhosis and hepatocellular carcinoma. The underlying cause of MASH is multifactorial, but accumulating evidence indicates that the inflammatory process in the hepatic microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…Thus, it is concluded that the low chronic inflammatory level in adipose tissue, perpetuated due to the accumulation of fat-lipogenesis-which contributes to the accentuation of obesity, contributes to the establishment of the pathogenesis of metabolic disorders, such as MAFLD [176,177]. In this sense, the inflammatory process in adipose tissue is characterized by the infiltration of macrophages and activation of inflammatory pathways mediated mainly by NF-κB and by adipokines, hepatokines, and myokines by endocrine, autocrine, and paracrine pathways, correlating with high serum levels of pro-inflammatory adipokines, such as leptin and resistin, low concentrations of anti-inflammatory adipokines, such as adiponectin, vaspin, and omentin, and high levels of hepatokines (fetuin-A) and pro-inflammatory myokines (irisin and IL-6), constituting the profile of organokines in the context of obesity [178,179].…”
Section: Hepatokinesmentioning
confidence: 99%
“…Thus, it is concluded that the low chronic inflammatory level in adipose tissue, perpetuated due to the accumulation of fat-lipogenesis-which contributes to the accentuation of obesity, contributes to the establishment of the pathogenesis of metabolic disorders, such as MAFLD [176,177]. In this sense, the inflammatory process in adipose tissue is characterized by the infiltration of macrophages and activation of inflammatory pathways mediated mainly by NF-κB and by adipokines, hepatokines, and myokines by endocrine, autocrine, and paracrine pathways, correlating with high serum levels of pro-inflammatory adipokines, such as leptin and resistin, low concentrations of anti-inflammatory adipokines, such as adiponectin, vaspin, and omentin, and high levels of hepatokines (fetuin-A) and pro-inflammatory myokines (irisin and IL-6), constituting the profile of organokines in the context of obesity [178,179].…”
Section: Hepatokinesmentioning
confidence: 99%